Insomnia and Suicide-Related Behaviors: A Multi-Study Investigation of Thwarted Belongingness as a Distinct Explanatory Factor - Chu, Carol (J Affect Disord, 2016)
BACKGROUND: Insomnia is a robust correlate of suicidal ideation and behavior. Preliminary research has identified thwarted belongingness (c.f. social disconnection) as an explanatory link between insomnia and suicidal ideation. OBJECTIVES: This study replicates and extends previous findings in four demographically diverse samples using both cross-sectional and longitudinal designs. Additionally, the specificity of thwarted belongingness was evaluated by testing anxiety as a rival mediator. METHOD: Self-report measures of insomnia severity, thwarted belongingness, suicidal ideation and behavior, and anxiety were administered in four adult samples: 469 undergraduate students, 352 psychiatric outpatients, 858 firefighters, and 217 primary care patients. RESULTS: More severe insomnia was associated with more severe thwarted belongingness and suicidality. Thwarted belongingness significantly accounted for the association between insomnia and suicidality, cross-sectionally and longitudinally, beyond anxiety. Notably, findings supported the specificity of thwarted belongingness: anxiety did not significantly mediate the association between insomnia and suicidality, and insomnia did not mediate the relation between thwarted belongingness and suicidality. LIMITATIONS: This study relied solely on self-report measures. Future studies incorporating objective sleep measurements are needed. CONCLUSION: Findings underscore the utility of assessing and addressing sleep disturbances and social disconnection to reduce suicide risk.